Low Knowledge and Negative Perception about the Risks of Breast Cancer among Female High School Students - Sri Yusnita Irda Sari; Dini Desmona; Teguh Marfen Djajakusumah (Althea Medical Journal, 2019)
Background: Breast cancer is one of the leading causes of death among women. The potential risk factor is older age, however, the prevalence at a young age is recently increased. Unfortunately, young women show a poor level of knowledge about breast cancer. This study aimed to explore the knowledge and perception among female high school students about the risks of breast cancer.Methods: This cross-sectional study was conducted from October to November 2013 in Jatinangor. One hundred and eighteen (n118) female students from three senior high schools were included in this study. Data on mother’s educational status, family income, family history of breast cancer and number of a family members living in the same house was collected. Knowledge and perception toward risks of breast cancer were assessed using a validated questionnaire.Results: Most of the students (69.5%) had a poor level of knowledge about breast cancer. Furthermore, they also had a negative perception (43.2%) toward breast cancer’s risks. Factor influencing their perception was family income (p=0.012) and knowledge about breast cancer (p=0.008).Conclusions: Young female high school students have low knowledge and negative perception about the risks of breast cancer. It is recommended that education about breast care and breast cancer should be given to high school female students to improve their knowledge and to early detect abnormality in their breast.